Read-Out Interfacing Circuit for ISFET Ionic Concentration Measurement: article / Turki Abdulmajid Abdo Al-Qutami - Abdo Al-Qutami, Turki Abdulmajid (2009)
This paper is focused on designing a read-out interfacing circuit (ROIC) which has the ability to measure the ionic concentrations by interfacing it with an electrochemical sensor called ISFET the ion-sensitive field-effect transistor. ISFET is fabricated to detect specific ionic concentrations and for this case the ISFET used was the one to measure the PH level in the solution. The ISFET is tested under different conditions such as temperature, biasing voltage and different values of components and how these readings are different between simulation and actual hardware. The ROIC is connected to a microcontroller based-system that measures the output voltage from it and keeps a record of the data. The softwares used were LTspice for simulation, Proteus for PCB design and Arduino microcontroller. The ROIC designed to measure the ionic concentration was constant voltage constant current (CVCC). The IROC was tested under different parameters value of the circuit. Some parameters had an effect of increasing or decreasing on the output voltage from ROIC. The ISFET sensor itself had been investigated under different conditions. It was observed that ISFET is affected by temperature and its fabrication characterization.